Is Family Provision’s Limitation to Testamentary Freedom Justified or Not? - Pingping Wang (Law and Economy, 2023)
Testamentary freedom is a fundamental principle in testamentary inheritance and bequests, and it is a principle that is generally accepted in all countries of the world. The theoretical basis of testamentary freedom derives from the autonomy of will in civil law, a principle that was developed considerably in the Age of Enlightenment. Family provision is a subsequent development that limits the freedom of testamentary freedom. This essay analyzes the content of family provision, the value of testamentary freedom and family provision, and the nature of testamentary freedom from three perspectives, and shows that only freedom based on rules is true freedom. It is argued that family provision is justified to restrict the principle of testamentary freedom.